2010
DOI: 10.1128/jcm.01390-10
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasma capsulatum Prosthetic Valve Endocarditis with Negative Fungal Blood Cultures and Negative Histoplasma Antigen Assay in an Immunocompetent Patient

Abstract: We report a case of Histoplasma capsulatum endocarditis in which Histoplasma antigen assay and fungal blood cultures were negative. The diagnosis was made by microscopic examination and culture of the excised valve. Histoplasma capsulatum should be considered in the differential diagnosis of culture-negative endocarditis in regions where it is endemic and in travelers. CASE REPORTThe patient, a 59-year-old female living in northeastern Ohio, with a history significant for coronary artery disease, hypertension,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Secondly, the uncommon causative microorganism H. capsulatum has shown to be diagnostically challenging [7,8]. The time between the onset of symptoms and diagnosis is delayed to up to 9 months, and it has therefore been associated with a high risk of mortality in prosthetic valve endocarditis (PVE) [8].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the uncommon causative microorganism H. capsulatum has shown to be diagnostically challenging [7,8]. The time between the onset of symptoms and diagnosis is delayed to up to 9 months, and it has therefore been associated with a high risk of mortality in prosthetic valve endocarditis (PVE) [8].…”
Section: Discussionmentioning
confidence: 99%
“…Commercial tests that detect fungal wall antigens such as galactomannan [2,61,62] and β-1,3-D-glucan [62] can show good sensitivity and specificity in diagnosis of fungal CNE. Jinno et al [56] reported negative urine Histoplasma antigen results in their patient with H. capsulatum CNE, with diagnosis based on valvular pathology and tissue culture.…”
Section: Cne Due To Fungal Pathogensmentioning
confidence: 97%
“…Among cases in the recent literature, infections with Aspergillus spp. [53][54][55], Histoplasma capsulatum [56][57][58] and Trichosporin spp. [59,60] are the most widely reported.…”
Section: Cne Due To Fungal Pathogensmentioning
confidence: 99%
“…Epidemiological surveillance definitions of HAI include surgical site infections associated with surgical implants or medical indwelling devices, when they occur within 30–90 days after the surgical procedure [ 4 ]. Clinically, H. capsulatum infections have been identified in individuals with invasive devices or surgical implants, and some authors have described endovascular histoplasmosis in patients with vascular prosthetic or synthetic implants [ 80 , 81 , 116 119 ]. Usually, the diagnosis is made by isolation of the fungus in vegetation or over synthetic materials.…”
Section: Biofilm Formationmentioning
confidence: 99%
“…Usually, the diagnosis is made by isolation of the fungus in vegetation or over synthetic materials. In addition, histopathological observation has revealed fibrin, large aggregates of yeast cells, mild chronic inflammatory cell infiltrates (predominantly macrophages) [ 80 , 116 , 118 ], and H. capsulatum hyphae (M-phase) in a few cases [ 117 ]. Furthermore, H. capsulatum endocarditis has also been described in native heart valves [ 118 120 ].…”
Section: Biofilm Formationmentioning
confidence: 99%